Fermi, Pasta, Ulam and the birth of experimental mathematics - Porter, M; Zabusky, N; Hu, B; Campbell, D (2009)
Enrico Fermi, John Pasta, and Stanislaw Ulam's discovery of numerical experiment of nonlinear problem continues to inspire researchers. The Los Alamos scientists call this problem as MANIAC (MAthematical Numerical Integrator And Computer) and performs brute force numerical computations. Fermi, Pasta, Ulam's (FPU) original investigation can be described as the birth of experimental mathematics, which led to computer based investigations designed to give insights into complex mathematical and physical problems. Studies such as atomic lattices of solid state physics are highly inspired by FPU problem of nonlinear systems. FPU problems have also led to the creation of concepts like chaos, solitons and breather's invention, development, refinement and application to a number of real world systems. It also reveals facts on a remarkably broad range of topics in nonlinear dynamics, statistical mechanics and computational physics.